2019
DOI: 10.3389/fphar.2019.00767
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Flow in Corpus Luteum Measured by Transvaginal Two-Dimensional and Three-Dimensional Ultrasound in the Prediction of Early Intrauterine Pregnancy Outcomes

Abstract: Objective: The purpose of this study was to explore the application of transvaginal two-dimensional and three-dimensional power Doppler ultrasound in pregnancy corpus luteum to predict the final outcome of early intrauterine pregnancy. Methods: This is a prospective observational cohort study. Six hundred early intrauterine pregnant women in Shanghai Changning Maternity and Infant Health Hospital were selected as the research objects from January 2015 to December 2015. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The mechanisms through which different routes of exogenous progesterone may act synergistically have not been fully clarified. In natural conception, the corpus luteum secretes progesterone into microvessels that feed into the pelvic vasculature and, in turn, the systemic circulation ( Takasaki et al , 2009 ; Han et al , 2019 ). It is thus plausible to consider that low serum progesterone levels may constitute a proxy marker of a hypoprogestogenic state and insufficient luteal support ( Verhaegen et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms through which different routes of exogenous progesterone may act synergistically have not been fully clarified. In natural conception, the corpus luteum secretes progesterone into microvessels that feed into the pelvic vasculature and, in turn, the systemic circulation ( Takasaki et al , 2009 ; Han et al , 2019 ). It is thus plausible to consider that low serum progesterone levels may constitute a proxy marker of a hypoprogestogenic state and insufficient luteal support ( Verhaegen et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its high‐frequency probe can significantly improve the resolution, thus showing clearer images of pelvic organs, and showing blood flow information such as vascular morphology and microvascular perfusion at the scar. This method has a wide range of application, without requirement of holding urine and waiting and without interference from obesity, abdominal scar, and intestinal gas and other problems [22] 25 . Color Doppler ultrasound is also an effective means of diagnosing CSP, which is safe, rapid, and accurate 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This method has a wide range of application, without requirement of holding urine and waiting and without interference from obesity, abdominal scar, and intestinal gas and other problems [22]. 25 Color Doppler ultrasound is also an effective means of diagnosing CSP, which is safe, rapid, and accurate. 26 Transvaginal color Doppler ultrasonography can more clearly show the size of the uterus, the location, and specific condition of CSP, contributing to the analysis of the internal uterine bleeding in patients and subsequent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If pregnancy is achieved, the RI remains low at approximately 0.45 and continues to remain so during the first trimester until the luteal-placental shift occurs. Han et al [ 28 ] showed that increased PI and RI in the blood flow surrounding the corpus luteum during the first trimester was associated with pregnancy termination. The meaning of Doppler that can be used clinically is summarized in Table 1 .…”
Section: Ovarian Blood Flowmentioning
confidence: 99%